Therapeutic exercises in the combination therapy of patients with juvenile chronic arthritis - Tatyana Andreyevna Shelepina (Современная ревматология)
The paper analyzes the role of therapeutic exercises in the therapy of patients with juvenile chronic arthritis. The author discusses the time of, indications for, and contraindications to their use and states her belief that it is advisable for a rheumatologist to prescribe this therapy option. The data available in the literature and the author’s data on the efficiency of this therapy are given.